Just What I See? Implications of Congruence Between Supervisors’ and Employees’ Perceptions of Pay Justice for Employees’ Work-Related Attitudes and Behaviors - Malmrud, Sofia; Falkenberg, Helena; Eib, Constanze; Hellgren, Johnny; Sverke, Magnus (Frontiers in Psychology, 2020)
Perceiving a pay system as just has been suggested to be a precondition for individualized pay to have a motivating effect for employees. Supervisors’ enacted justice is central for understanding the effects that pay setting can have on employee attitudes and behavior. Yet, enacted justice has received little research attention, both in regard to organizational justice and pay-related topics. This study examines the effects of employees’ perceived pay justice and supervisors’ enacted justice, as well as the degree of congruence, on employees’ work-related attitudes and behaviors. Questionnaire data from employees (N=566) matched with data from their pay-setting supervisors (N=208), employed in a Swedish manufacturing company, was analyzed. Results of polynomial regression with response surface analysis show that employees’ perceptions of pay justice were important for their work-related attitudes and behaviors and that supervisor–employee congruence regarding pay justice was positively related to employees’ attitudes and behavior, particularly when the ratings concerned high levels of justice. The results not only highlight the importance of developing a pay system that is perceived as just by employees, but also emphasize the importance of reaching a congruence between supervisors’ and employees’ perceptions of high fairness, as this has positive implications for employees’ attitudes and behaviors.